PREVALENCE AND ASSOCIATED RISK FACTORS OF LOW BONE MINERAL DENSITY IN MALAYSIANS LIVING WITH HIV: A CROSS-SECTIONAL STUDY - Sun, Choon Peng; Shanty, Velaiutham; Wong, Peng Shyan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION The global impact of HIV/AIDS has led to improved survival rates due to treatment efforts, but it has also resulted in a rise in chronic comorbidities such as low bone mineral density (BMD). Contributing factors to low BMD in HIV-positive individuals include the virus itself, treatment, and lifestyle factors. This study aims to describe the prevalence of low BMD and associated risk factors among individuals living with HIV. Findings from this research can potentially influence future screening practices. METHODOLOGY This cross-sectional study involved patients aged 25-45 years old with HIV undergoing follow-up in an infectious disease clinic. Participants underwent DXA scans to evaluate bone density, with T scores used to categorize BMD levels according to WHO criteria. Data were analysed to determine associations between low BMD and various risk factors. RESULT The study found that 65.5% (226 out of 345) of patients had low BMD, with 91.1% (206) having osteopenia and 8.2% (20) having osteoporosis. Binary logistic regression analysis revealed associations between low BMD and male gender and lower BMI. Additionally, BMD was observed to improve with a longer duration of antiretroviral therapy (ART). CONCLUSION The study underscores the high prevalence of low BMD among people living with HIV, emphasizing the need for vigilance, particularly among those with risk factors such as low BMI and male gender. Therefore, it is crucial to pay attention to this population subgroup, promote a healthy lifestyle, normal body weight, and adherence to antiviral medication to enhance overall bone health.